Investigation of In Vitro Amoebicidal Activities of Trachystemon orientalis on Acanthamoeba castellanii Cysts and Trophozoites - Bülent Kaynak; Zeynep Kolören; Ülkü Karaman (Van Tıp Dergisi, 2019)
INTRODUCTION: Acanthamoeba species cause important diseases such as Acanthamoeba keratitis, granulomatous amoebic encephalitis and cutaneous acanthamoebiasis. In this study, we investigated the amoebicidal action of methanol and ringer extracts of Trachystemon orientalis plant on cyst and trophozoite forms of Acanthamoeba castellanii by evaluating cell viability percentage and IC50 values. METHODS: The in vitro amoebicidal effects of T. orientalis methanol and ringer extracts prepared at different concentrations on A. castellanii trophozoites and cysts were investigated. RESULTS: The IC50 value of A. castellanii trophozoite form at 72nd, 48th, 24th, 8th, 6th, 3rd and 1st hours were 4, 7.2, 8.7, 11.1, 14.1, 21.4, and 23.8 mg/mL with methanol extract of T. orientalis, respectively, and 8.5, 11.1, 14.4, 15.9, 20.9, 23.9 and 25.8 mg/mL, with ringer extract of T. orientalis respectively. T. orientalis 80 mg/mL methanol extract showed lethal effect for the all trophozoites at 72nd hour. The viability (%) of the ringer extract of T. orientalis at 72nd hour was 1.6 +- 0.3. DISCUSSION AND CONCLUSION: Methanolic extract of T. orientalis was found to be more effective than ringer extract on Acanthamoeba trophozoites. A. castellanii cysts showed similar sensitivity to methanolic and ringer extracts of T. orientalis. Both extracts showed greater amoebicidal activity on trophozoites when compared to cysts. Whether the concentrations explored in the existing study are cytotoxic for mammalian cells, or have toxic effects on experimental animals should be examined with future in vivo studies. Furthermore, the mechanism of action for the active substances responsible for biological activity should be investigated in future studies.